The khat dilemma in Jimma area: The socio-economic analysis of benefits and harms associated with khat use - Fojo, Gudina Abashula; Tesfa, Abulu (Harmoni Sosial: Jurnal Pendidikan IPS, 2020)
This study aims to come up with empirically based evidence concerning the dilemma of khat (Catha edulis Forsk, a natural green leaf used as a stimulant. This study carried out in selected areas in the Jimma Zone, Oromia National Regional State, South West Ethiopia, in order to clarify the dilemma to use it based on empirical evidence concerning its socio-economic benefits and harms. To this end, 397 samples selected randomly using a probability sampling method from the study areas and a survey undertaken using closed and open-ended questionnaires. Moreover, key informant interviews and focus group discussions carried out in order to collect qualitative data to supplement the survey study. Descriptive statistics like percentages mean and inferential statistics, such as chi-square used to analyze the quantitative data. On the other hand, the thematic analysis used to analyze the qualitative data. The result showed that the respondents had experienced various types of problems they attributed to khat use. As far as the specific economic problems experienced by the respondents were concerned, they were unable to be punctual on work, absent from work, and exposed to unnecessary costs. Moreover, the respondents said that they were unable to save money daily, weekly, or monthly due to expenses attributed to khat chewing. As far as its social harm is concerned, the study participants said that they experienced conflict between themselves and their families due the fact that khat use costs interfered with their families' basic needs expenses. Some of them also mentioned that they conflicted with their bosses because they were not punctual and absent from work due to khat chewing. Similarly, the FGD participants from the community argued that khat chewing has become forcing the jobless segments of the community, mainly to engage in anti-social behaviors such as theft and robbery.